Late Cretaceous to Recent kinematics of SE Anatolia (Turkey) - Kaymakci, N.; Inceoz, M.; Ertepinar, P.; Koc, A. (Geological Soc Publishing House, 2010)
Five different deformation phases have been recognized in the SE Anatolian orogen and the Arabian Platform based on palaeostress inversion studies using fault-slip data sets. The timing and duration of these phases are determined using various criteria including the age of the affected strata, syndepositional structures, cross-cutting structures and overprinting slickensides. The oldest deformation phase is characterized generally by NE-SW-directed extension. The extension is thought to have resulted from slab-roll back processes during the Maastrichtian to Middle Eocene interval (c. 60 Ma to 40-35 Ma). The second deformation phase is characterized by east-west to NW-SE-directed compression and thought to result from cessation of roll-back processes possibly due to subduction of younger oceanic crust or increase in the convergence rate between Africa and Eurasia during the post-Middle Eocene to Late Oligocene interval (c. 40-35 Ma to 25 Ma). The third deformation phase is characterized by east-west to NW-SE-directed extension possibly due to slab detachment that initiated in Iran and migrated westwards during the latest Oligocene to Middle Miocene period (25-11 Ma). The fourth deformation phase is characterized by approximately north-south-directed compression due to collision and further northwards indentation of Arabian Plate by the end of Middle Miocene (11-3.5 Ma). The fifth and present deformation phase is characterized by NE-SW compression which might result from tectonic re-organization in the region since the Middle Pliocene (c. 3.5 Ma to recent).
Keywords: Black-Sea; Sedimentary Basins; Neogene Evolution; Malatya Basin; Subduction; History; Western; Arc; Deformation; Lithosphere